Traumatic Memory in Mahfud Ikhwan’s Dawuk Dwilogy as a Cultural Manifestation of East Java's Northern Coastal Communities - Alifian, Muhammad Afnani; Saryono, Djoko; Karkono; Rahman, Norhayati Ab. (Universitas Muhammadiyah Malang, 2024)
Traumatic memory can become a manifestation of a community's cultural wisdom when the community collectively continues to maintain fear of the object of trauma. Mahfud Ikhwan's Dwilogi Dawuk novel tells the story of traumatic memory rooted in the community's trauma to the livelihood of blandong and the forestry ministry that has been maintained for generations. The purpose of this study is to describe the symptoms of trauma in the Dawuk duogy experienced by the characters to produce findings that traumatic memory can become the cultural wisdom of the community. The data of this research are novel texts in the form of character utterances, narrator monologues, and dialogues between characters. The source of the research data is the Dawuk bilingual novel, namely Dawuk; The Gray Tale of Rumbuk Randu and Anwar Tohari Mencari Mati. Data collection is done with documentation technique. The main instrument in the research is the researcher himself who is supported by a data search grid table. The flow of data analysis in this study, namely (1) data collection, (2) data condensation, (3) data presentation, and (4) conclusion drawing. Once collected, the data were analyzed based on the research focus of traumatic memory symptoms. The results showed that flashback symptoms were experienced when the characters and people of Rumbuk Randu felt, heard, and recalled the traumatic events. Nightmare symptoms occur to characters who feel fear of the traumatized object while in an unconscious state. Meanwhile, the repetitive phenomenon occurs when the Rumbuk Randu community equates current events with bad events in the past. Based on the research results, it can be concluded that this novel is a medium for conveying traumatic memory symptoms about the conflict between blandongan and the forestry ministry on the north coast of East Java, precisely in the Lamongan area.